EDUCATE A WOMAN, EMPOWER A NATION: THE ROLE OF EDUCATION IN WOMEN'S SOCIOECONOMIC ADVANCEMENT IN AFGHANISTAN - Quraishi, Tamanna; Faizi, Fatana; Shewa, Faiza; Shewa, Homa; Sadat, Adiba; Moradi, Shamsia (International Journal of Multidisciplinary Research and Literature, 2025)
Education is widely acknowledged as a transformative tool for women’s empowerment and national development. In Afghanistan, access to higher education for women remains limited due to socio-cultural, economic, and political constraints. This study aimed to explore the role of education in advancing the socioeconomic status of Afghan women, particularly those enrolled at the Vision Higher Education and Research Institute, which serves female students across various faculties, including medicine, computer science, economics, arts, and journalism. Using a structured questionnaire distributed via WhatsApp, email, Facebook, and the institute’s online portal, responses were collected from 200 participants aged between 20 and 30. The survey focused on motivations for pursuing higher education, family support, challenges faced, and the influence of digital learning. Results indicated strong motivation among women for career advancement and financial independence, with significant family support reported. However, barriers such as cultural expectations and limited access to technology persist. The findings underscore the importance of supportive environments and digital platforms in enhancing educational access and impact. In conclusion, education plays a vital role in empowering Afghan women socially and economically. Comprehensive support and innovative educational solutions are essential to overcoming existing challenges and fostering gender equality.